2021
DOI: 10.3390/ijms22041642
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline Impact on Redox Homeostasis of Normal Human Melanocytes HEMn-LP Exposed to UVA Radiation and Hydrogen Peroxide

Abstract: Minocycline is a semisynthetic tetracycline antibiotic. In addition to its antibacterial activity, minocycline shows many non-antibiotic, beneficial effects, including antioxidative action. The property is responsible, e.g., for anti-inflammatory, neuroprotective, and cardioprotective effects of the drug. However, long-term pharmacotherapy with minocycline may lead to hyperpigmentation of the skin. The reasons for the pigmentation disorders include the deposition of the drug and its metabolites in melanin-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 91 publications
0
13
0
Order By: Relevance
“…Lightly pigmented melanocytes were more sensitive to minocycline. In this case, EC 50 was calculated to be about 48 µM [ 49 ]. The observed difference for darkly and lightly pigmented melanocytes suggests that a high content of melanin may protect cells from the tetracycline-induced adverse effect.…”
Section: Discussionmentioning
confidence: 99%
“…Lightly pigmented melanocytes were more sensitive to minocycline. In this case, EC 50 was calculated to be about 48 µM [ 49 ]. The observed difference for darkly and lightly pigmented melanocytes suggests that a high content of melanin may protect cells from the tetracycline-induced adverse effect.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that lightly pigmented melanocytes (HEMn-LP) appeared to be more sensitive to minocycline. Recently published study indicated the EC 50 value was two-times lower for lightly pigmented melanocytes then obtained for darkly pigmented cells [44]. The difference suggests that melanin may protect cells from toxic effects of minocycline.…”
Section: Discussionmentioning
confidence: 91%
“…Our preliminary study of minocycline revealed that the drug significantly increased melanin content and the activity of tyrosinase—the key enzyme of melanogenesis. Besides, it triggered the supranuclear accumulation of tyrosinase, similar to UVA and UVB radiation [ 75 , 76 ].…”
Section: Chemical and Biological Basis Of Photosensitivitymentioning
confidence: 99%